Analysis and biophysical modelling of baroreflex stimulation with applications in syncope and falls : a neural engineering approach - Finucane, Ciarán (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Medical Gerontology, 2011)
Carotid Sinus Hypersensitivity (CSH) is an age related disorder, and a common cause of recurrent falls and syncope in the elderly. CSH is prevalent in patients with Dementia and Parkinson's disease and is a strong predictor of poor cognitive function compared to traditional risk factors such as stroke and hypertension. CSH is diagnosed in patients with unexplained falls or syncope, when carotid sinus massage (CSM) is accompanied by asystole greater than 3 seconds (cardioinhibitory subtype - CICSH) or a fall in systolic blood pressure greater than SOmmHg (vasodepressor subtype - VDCSH), or both (MXCSH subtype) and no competing diagnosis. When symptomatic i.e. accompanied by loss of consciousness. Carotid Sinus Syndrome (CSS) is diagnosed. CSH is one of a number of so-called Neurocardiovascular instabilities (NCVI's) known to affect the older adult. Other NCVI's include orthostatic hypotension (OH) and vasovagal syncope (VVS). NCVI's are typically characterised by abnormal cardiovascular control leading to intermittent bouts of hypotension and/or bradycardia. The underlying pathophysiology of CSH is not well understood, although a number of hypotheses have been proposed.
Keywords: Medical Gerontology, Ph.D.; Ph.D. Trinity College Dublin